Moral Cognition and Emotional Regulation in Islamic Religious Learning at Madrasah Ibtidaiyah by Phenomenological Approach - Sadam Fajar Shodiq; Nurul Aisyah (Universitas Islam Negeri (UIN) Salatiga, 2026)
Objectives: This research aims to explore the construction of moral cognition and emotional regulation in Madrasah Ibtidaiyah (Islamic Primary School) students during Islamic Religious Education (IRE), with a focus on their lived experiences in daily classroom interactions. Method: A qualitative descriptive phenomenological approach was employed. Students aged 8–11 years and Islamic Religious Education teachers from Madrasah Ibtidaiyah Jogonalan in Yogyakarta, Indonesia, were selected as research participants. Data were collected through classroom observations, semi-structured interviews, and document analysis. Analysis followed Colaizzi’s phenomenological method to identify essential experiential themes. Results: The findings indicate that students construct moral meaning through concrete, relational, and religiously grounded experiences rather than abstract reasoning. Emotional regulation appears developmental and context-dependent, marked by performance-related anxiety and shaped through teacher-mediated classroom interactions. Theoretical Contribution: This study provides phenomenological insight into the co-emergence of moral cognition and emotional regulation within Islamic elementary education. The findings extend developmental perspectives by highlighting the role of teacher co-regulation in Islamic faith-based learning environments. Implication: Islamic Religious Education classrooms can be understood as moral–emotional learning spaces where relational pedagogy plays a crucial role. Emotion-sensitive and dialogical teaching practices may support more meaningful moral internalization in Madrasah Ibtidaiyah contexts.